Growth of few layer graphene from commercial C2 hydrocarbons at low temperature and controlled surface functionalization. Issue 4 (2nd April 2016) - Khajehmandali, Saeid; Angaji, Mahmoud Torabi; Rashidi, Ali Morad
ABSTRACT: Graphene is mostly grown from methane on copper foils at a high temperature about 1000°C. In this research, a commercial ethylene-acetylene-ethane mixture was used as a clean precursor for graphene synthesis on nickel foils in a chemical vapor deposition reactor at 750°C. Furthermore, controlled functionalization of graphene sheets was achieved via hydrothermal oxidation at moderate pressure and temperature using nitric acid. Broadened 2D band and G band frequencies in Raman spectra indicated that pristine graphene (PG) was of high quality with low defects. X-ray diffraction results confirmed that PG has five layers. Transmission electron microscopy and N2 adsorption-desorption analyses affirmed that the graphene is of a good quality, large surface area (562 m 2 /g) and small pore size. Fourier transform infrared spectroscopy confirmed functionalization process performance. Thermogravimetric analysis affirmed that the thermal stability of PG was drastically decreased after the functionalization process.